2007
DOI: 10.1002/pam.20290
|View full text |Cite
|
Sign up to set email alerts
|

Child care quality in different state policy contexts

Abstract: Using data from the Child Care Supplement to the Fragile Families and Child Wellbeing Study, we test associations between the quality of child care and state child care policies. These data, which include observations of child care and interviews with care providers and mothers for 777 children across 14 states, allow for comparisons across a broader range of policy regimes and care settings than earlier research on this topic. Using multilevel linear and logistic models, we found that more generous subsidy po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 35 publications
2
60
0
1
Order By: Relevance
“…According to the theoretical principles of life course health development, health development is a multilevel construct, and the FFCWS measures children's social environments at many of the levels that influence their health development throughout the life course: the family (both biological parents and the social unit that comprises the household) (Jackson et al 2012;Pilkauskas 2014), childcare settings (Rigby et al 2007), schools (Razza et al Forthcoming), neighborhoods (Suglia et al 2013), and broader contexts such as states or local labor markets (Rigby et al 2007;Pilkauskas et al 2012).…”
Section: The Ffcws and Life Course Health Development Researchmentioning
confidence: 99%
“…According to the theoretical principles of life course health development, health development is a multilevel construct, and the FFCWS measures children's social environments at many of the levels that influence their health development throughout the life course: the family (both biological parents and the social unit that comprises the household) (Jackson et al 2012;Pilkauskas 2014), childcare settings (Rigby et al 2007), schools (Razza et al Forthcoming), neighborhoods (Suglia et al 2013), and broader contexts such as states or local labor markets (Rigby et al 2007;Pilkauskas et al 2012).…”
Section: The Ffcws and Life Course Health Development Researchmentioning
confidence: 99%
“…For a sample of low-income mothers, Press et al (2006) reported that employed mothers were more likely to feel depressed when they preferred different child care because of low quality of the care. Despite their different research focus, the sensitivity analyses of Rigby et al (2007) also show moderate correlations between female labor force participation and the stringency of US state policies for the quality of child care centers. These studies, however, were based only on cross-sectional measures of quality regulations, maternal child care satisfaction, employment, or subjective well-being, which may be endogenous.…”
mentioning
confidence: 98%
“…In addition, CCDF funds were designated to enhance the quality of child care available to families through support services, such as the Child Care Resource and Referral network, and the creation of more stringent licensing and regulation programs (Rigby et al 2007). Though states have discretion on how to distribute CCDF funds to families, the majority of funding is for TANF (Temporary Assistance for Needy Families) recipients or other qualified low income families to access child care while parents work or seek work (Vesley and Anderson 2009).…”
Section: The Us Perspective On Child Care Policymentioning
confidence: 99%